CHANGES IN THE PHAGOCYTIC ACTIVITY OF LEUKOCYTES AND THE LEVEL OF C-REACTIVE PROTEIN AS PATHOGENIC FACTORS OF THE INFLAMMATORY PROCESS IN PERIODONTIUM SECONDARY TO THE USE OF METAL CROWNS - Marfiian, Oleh V.; Demkovych, Andrii Ye.; Bandrivska, Orysia O.; Bedenyuk, Oleksandr A. (Eastern Ukrainian Medical Journal, 2026)
The aim of the study: The aim of this work was to investigate changes in the phagocytic activity of leukocytes and the level of C-reactive protein in experimental periodontitis of bacterial-immune genesis under the condition of using different types of metal crowns.Materials and methods. The study was conducted on clinically healthy male white rats weighing 150–200 g, which were kept in a vivarium in compliance with sanitary and hygienic standards and requirements of good laboratory practice (GLP). The experimental animals were divided into four groups: Group I – intact animals (n = 10); Group II – animals with periodontitis (30th day of the experiment, n = 8); Group III – animals with periodontitis, which were installed with stamped crowns for periodontitis (30th day of the experiment, n = 8); Group IV – animals with periodontitis, which were installed with cast crowns for periodontitis (30th day of the experiment, n = 8).Bacterial-immune periodontitis was modeled by injecting a mixture of Staphylococcus aureus and Streptococcus hemolyticus microorganisms suspended in egg white into periodontal tissues. To produce permanent structures, impressions were taken from the central incisors of the lower jaw of experimental animals using Speedex silicone impression material and crowns were fabricated using standard techniques.To study the phagocytes activity of leukocytes, it was determined by counting the number of neutrophils in smears and expressed as phagocytic number. The level of C-reactive protein (CRP) in serum was determined by enzyme-linked immunosorbent assay. Data processing was carried out using non-parametric statistical methods in STATISTICA 10.0 software (StatSoft, USA).Results. Analysis of the dynamics of the phagocytic number of blood granulocytes in animals with periodontitis under the conditions of using cast crowns showed that on the 30th day of the experiment this indicator was significantly higher – by 1,48 times, p<0,001, compared to the intact group. It was also found that the phagocytic number slightly exceeded the value in animals with an inflammatory process without prosthetics by 1.07 times, p<0.05. At the same time, this indicator was lower by 1,07 times, p<0,01, compared to similar data obtained in rats with stamped crowns.The content of C-reactive protein, on the 30th day of the experiment, in the blood serum of experimental animals with periodontitis of bacterial-immune genesis, exceeded by 1,40 times, p<0.001, the indicators that were in the animals of the intact group. In experimental animals after prosthetics with stamped crowns, the content of CRP was significantly increased compared to the data of the intact and the groups with periodontitis of bacterial-immune genesis – by 1.83 times and by 1.30 times, respectively, p<0,001.A similar trend was observed in the blood serum of animals with cast structures: the CRP content significantly increased – by 2,14 times, p<0,001, compared to intact animals; by 1,53 times, p<0.001, compared to the group with simulated periodontitis on the 30th day without crowns and by 1,17 times, p<0,01, in animals with fixed stamped structures.Conclusion. Thus, as a result of the study, it was found that on the 30th day of periodontitis of bacterial-immune genesis, activation of the immune response was observed with a significant increase in phagocytic activity in the experimental groups using fixed dentures, which indicates an increase in the inflammatory reaction, probably due to mechanical irritation or microbial colonization around the dentures. The course of experimental periodontitis was also accompanied by an increase in the level of C-reactive protein in the blood serum, which indicates the presence of an inflammatory process, and the indicators obtained under the conditions of using fixed structures indicate a more adverse effect of integral prosthetics on this link in the development of the inflammatory process in the periodontal complex.